Cancer patterns, trends, and transitions in Peru: a regional perspective - Piñeros, Marion; Ramos, Willy; Antoni, Sébastien; Abriata, Graciela; Medina, Luis E; Miranda, J Jaime; Payet, Eduardo; Bray, Freddie (The lancet oncology, 2017)
Peru, like several other South American countries, is experiencing remarkable population growth, ageing, and urbanisation, which has given rise to profound changes in its epidemiological profile. Prostate and breast cancer are the most frequent cancers in men and women, respectively, in Lima and Arequipa, the two areas with population-based cancer registries. However, infection-associated cancers (cervix and stomach) are also common, and rank highest in the national cancer mortality profile. Although a foundation of surveillance informs cancer-control initiatives in Peru, improvements in the vital statistics system, and the quality and use of incidence data for the planning and assessment of cancer prevention and control actions, are needed. Existing population-based cancer registries in Lima and Arequipa, and linkages to the established national mandatory cancer reporting system, are crucial for the collection of high-quality data on national cancer incidence. The delivery of effective cancer prevention and control measures requires sustained investment in the collection of high-quality data capable of informing policies and driving research programmes.